THE CHARACTER DEVELOPMENT OF PHONEY BONE FROM BONE ONE VOLUME EDITION BY JEFF SMITH - Audi Ayuni; Sukri Adani (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This study aims to investigate the character development of Phoncible ‘Phoney’ Bone through the story based on his interactions with other characters, speech, behaviours, and visuals from the Bone comic series and link it to teach moral education to students. This study uses qualitative research as the research method, with psychoanalytic theory, to analyze the character development of Phoney Bone. This research shows that Phoney Bone has a greedy, selfish, self-centered, and manipulative personality. Based on the psychoanalytic theory of Sigmund Freud, Phoney Bone’s id shows that he is manipulative; his ego is shown alongside the id, which is fear of failing the action or getting consequences, and his superego shows when he cares about his cousins. From a moral, educational view, Phoney Bones's character portrays a negative moral personality; in teaching moral education, the teachers could use Phoney’s character to teach the students the consequences of actions.